2014
DOI: 10.1007/s00266-014-0353-z
|View full text |Cite
|
Sign up to set email alerts
|

Facelift Complications Related to Median and Peak Blood Pressure Evaluation

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…15 Studies have demonstrated that post-operative hematomas in surgery can occur frequently in the first 48 hours after surgery, but factors influencing these events are still not fully elucidated. 16, 17 One proposed theory is that inadequate post-operative pain control could lead to postoperative hypertension and possibly increase risk for bleeding. Better pain control, therefore, may reduce bleeding incidence, thus overruling the anti-platelet effects from NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies have demonstrated that post-operative hematomas in surgery can occur frequently in the first 48 hours after surgery, but factors influencing these events are still not fully elucidated. 16, 17 One proposed theory is that inadequate post-operative pain control could lead to postoperative hypertension and possibly increase risk for bleeding. Better pain control, therefore, may reduce bleeding incidence, thus overruling the anti-platelet effects from NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The association of elevated blood pressure with increased incidence of hematoma in facelifts has been well documented. [6][7][8][9][10][11] Baker et al demonstrated over a 30-year period a decreased hematoma rate from 8.7% to 3.97% in male facelifts with the implementation of perioperative blood pressure control. 3 Ramanadham et al reported a hematoma rate of 0.9% in a study of 1089 facelift patients treated with a perioperative medical regimen aimed to mitigate factors that precipitate elevated blood pressure, such as pain, anxiety, nausea, and exposure to anesthesia.…”
Section: Blood Pressurementioning
confidence: 99%
“…A 2014 retrospective review identified a history of hypertension, a preoperative SBP greater than 160 mm Hg, and an operating room peak SBP greater than 165 mm Hg as predictive risk factors for hematoma. 10 Strict perioperative blood pressure control, including preoperative clonidine administration, has been shown to reduce hematoma incidence in male patients. 4 , 6 Additionally, postoperative blood pressure control with intravenous labetalol and hydralazine significantly decreases the incidence of hematoma in both female and male patients.…”
Section: Common Complicationsmentioning
confidence: 99%